Identifikasi Kepatuhan Wajib Pajak dalam Membayar Pajak Bumi dan Bangunan di Kecamatan Cibiru Kota Bandung - Siti Selawati; Ai Siti Farida (Jurnal Perpajakan dan Keuangan Publik, 2022)
Land and Building Tax is a regional tax that has the largest contribution to regional development. The decreasing level of compliance in paying taxes and not achieving the realization of Land and Building Tax receipts are the problems found in this study. This study aims to determine the level of taxpayer compliance in paying Land and Building Tax in Cibiru District, Bandung City, the obstacles encountered and the efforts made by the Regional Government. This study uses a descriptive method with a qualitative approach. The results show that in the 2018-2020 range, taxpayer compliance in Cibiru District, Bandung City can be said to be quite obedient based on the realization of Land and Building Tax receipts for the last 3 years even though it always does not reach the target to be achieved. The obstacles found are that there are still taxpayers who do not pay taxes on time, and do not report changes in the subject or object of the tax to the tax officer. The local government's efforts are conducting socialization, putting up banners at road points, applying to attach proof of land and building taxes in full each time they will carry out government administration services to the Kelurahan, as well as an integrated operation program to make it easier for the community to pay Land and Building Tax.